A study on Integrated Marketing Communication (IMC) influences brand awareness of TM Point Senawang, Seremban / Nurzeela Razali - Razali, Nurzeela (2014)
The purpose of this study is to determine the factors that affecting the brand awareness of TM Point Senawang, Seremban. For this study the researcher chooses 100 respondents among the people and also the customer of TM Points itself. The objectives of this study aims to determine the relationship between advertising and brand awareness, to determine the relationship between promotion and brand awareness, to determine the relationship between personal selling and brand awareness and to examine the most contributing factor between brand awareness and IMC.Besides that, this study is a quantitative research study whereby the findings of the study were analyzed by using the Statistical Package for the Social Sciences (SPSS). Next, the data collected in this study is analyzed by using frequency, descriptive analysis, reliability, Pearson’s and correlat ion analysis in order to achieve the research objectives. Eventually, this study discovered that most of the respondents were female, the range of respondent age were 20 to 25 years old, the occupation mostly students, the education level among the respondent were Stpm/diploma and last but not least the income range is less than RM1500.There is also recommendation in this study which to improve the limitation of the study.